A review on the outbreak of termite (Coptotermes curvignathus) in rubber plantation / Muhammad Zubair Rosslan - Rosslan, Muhammad Zubair (Faculty of Plantation and Agrotechnology, 2017)
Termites have become one of the major pests that attack rubber and affected their economic life. The objectives of this study are to evaluate the termite infestation that causes damage in rubber plantation in Malaysia and also to evaluate the related factor that affect the termite infestation. Effect of termite infestation can be described based on the situation occurs at the rubber plantation. In order to prevent the termite outbreak, both good agricultural practices and integrated pest management should be applied. The termite starts to damage the rubber trees at any age and also cause damage in housing, forestry and also agriculture. Termite usually caused death of rubber trees in plantations. Termite often hollow out or ‘pipe’ the heartwood of the trunk once it attack rubber and most cases this may not fatal the tree but it does greatly reduce the value of the timber. Common indicator of severe C. curvignathus infestation recorded was extensive mud plastering around the bases of the tree trunks. There are many factors that contribute to the outbreak of termite such as food availability, fungal decay, history of wood damage, moisture content and temperature.